Private wars - Deocampo, Nick (Center for New Cinema, 2008)
Filipino filmmaker Nick Deocampo takes us on a deeply personal journey in search of a father whom he has not seen since childhood. Deocampo's grandfather was beheaded by the Japanese during World War II. His father then joined the revolutionary struggle against the Japanese occupation. After the war, an inability to find peace amid the horrors of war and the grandfather's death drove his father to alcohol and fits of drunken rage against his own family. Then one day, his father left home never to be seen again. Mixing documentary footage with reconstructed scenes, Deocampo takes his film crew on a detective search for his father, following leads from relatives, former guerilla members and other sources along the way.